La violencia en las escuelas - Moreno Artal, Edith (2012)
Schools must face a new challenge: the management of violence. Violence is a problem that has both social and psychological causes. This article outlines such causes in the light of the ideas of Martín-Baró and Bandura on this topic. These causes are properly fit into Costa Rican reality. Different alternatives to face the problem of violence in schools based on (1) experiences in other countries and (2) the course of action proposed by the Costa Rican Ministry of Education are offered. Because of its complexity, this problem requires an interdisciplinary effort from schools, community and families. The government should also encourage action to reduce social problems such as poverty and inadequate housing which affect many students´ families.